Media competencies of university professors and students. Comparison of levels in Spain, Portugal, Brazil and Venezuela - Romero-Rodríguez, Luis M; Contreras-Pulido, Paloma; Perez-Rodriguez, M. Amor (Cultura y Educación, 2019)
Media competencies are a set of skills that every individual should possess in order to be able to consume and produce media and digital and information products in a critical and analytical way. This exploratory and comparative work analyses the level of media competence among 1,676 university students and 524 professors in Brazil, Spain, Portugal and Venezuela. One of the main results shows that the level of knowledge of technology and interaction — which is linked to digital competencies — does not depend solely on age, thus contradicting theories of digital natives and migrants. Our study also found that the general level of media competence is no better than medium to low when considering language, technology, interaction, production and dissemination, ideology and values, and aesthetics. These results point to the need to develop transversal actions for instructing both university professors and students in media competencies to face an ecosystem dominated by fake news and disinformation, as well as public policies directed at improving these skills among citizens at large.
Las competencias mediáticas de profesores y estudiantes universitarios. Comparación de niveles en España, Portugal, Brasil y Venezuela
Las competencias mediáticas son un conjunto de habilidades que todo individuo debería poseer para poder consumir y producir información digital y mediática de manera crítica y analítica. En este artículo exploratorio y comparativo se analiza el nivel de competencia mediática de un grupo de 1676 estudiantes universitarios y 524 profesores universitarios de Brasil, España, Portugal y Venezuela. Uno de los resultados principales de nuestro trabajo demuestra que el nivel de conocimientos y de interacción tecnológicos — vinculado a las competencias digitales — no depende únicamente de la edad, lo que contradice las teorías de los nativos y migrantes digitales. Nuestro estudio también reveló que el nivel general de competencia mediática no supera el nivel medio-bajo si se tienen en cuenta aspectos como lenguaje, tecnología, interacción, producción y difusión, ideología y valores, y estética. Estos resultados ponen de relieve la necesidad de desarrollar acciones transversales para formar tanto a estudiantes como a docentes en materia de competencias mediáticas para que puedan enfrentarse a un ecosistema dominado por las noticias falsas y la desinformación, así como políticas públicas dirigidas a mejorar estas capacidades entre la población en general.
Keywords: media competence; digital literacy; university professors; university students; competencia mediática; alfabetización digital; profesores universitarios; estudiantes universitarios; Scopus